Development of Gamification Based Digital Comic Media for Pancasila Education in Elementary Schools - Nisrina Aura Andisa; Hamidaturrohmah Hamidaturrohmah (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This study aimed to develop a gamification-based digital comic as a learning medium for Pancasila Education for third-grade elementary school students and to determine its feasibility for use in learning. The study employed a Research and Development (R&D) approach using the 4D model, which consists of the define, design, develop, and disseminate stages. However, this research was conducted only up to the develop stage. The study was carried out at SDN 6 Tahunan and involved media experts, content experts, teachers, and third-grade students. Data were collected through observations, interviews, and questionnaires and were analyzed using descriptive quantitative techniques. The results showed that the gamification-based digital comic achieved a feasibility score of 83% from media experts and 85% from content experts, both of which were categorized as highly feasible. Teacher responses reached 82% and were also categorized as highly feasible, while student responses reached 76.04% and were categorized as feasible. The developed medium integrates contextual stories, visual illustrations, and gamification elements, such as points, challenges, and rewards, to create a more engaging and interactive learning experience. These findings indicate that the gamification-based digital comic meets the criteria of content suitability, visual presentation, language appropriateness, and ease of use. Therefore, it can serve as an innovative alternative learning medium for Pancasila Education in elementary schools